Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/1440-1681.12380
|View full text |Cite
|
Sign up to set email alerts
|

Can colonic migrating motor complexes occur in mice lacking the endothelin‐3 gene?

Abstract: In mammals, colonic migrating motor complexes (CMMC) are a major propulsive contraction responsible for the expulsion of faecal content. Mice with a mutation of the endothelin-3 gene raised on a 129SL background strain have ~70% colonic aganglionosis, lack CMMC, and are lethal within 12 days postpartum. In contrast, endothelin-3 mutant mice raised and maintained on a C57BL6 background strain (lethal-spotted (ls/ls) mice) can live for much longer, but it is unclear whether CMMC generation is preserved in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…However, 5‐FU treatment induced less severe damage to myenteric neurons with 12% loss at day 14 compared to 25% of myenteric neuronal loss at day 14 of oxaliplatin treatment . Although previous studies demonstrated that the loss of enteric neurons does not necessarily lead to changes in CMMCs our results demonstrated that the loss of myenteric neurons correlated with colonic dysmotility in 5‐FU‐treated mice. The loss of myenteric neurons leads to long‐term alterations in gastrointestinal functions as was shown in rats after cisplatin treatment and mice after oxaliplatin treatment .…”
Section: Discussioncontrasting
confidence: 59%
“…However, 5‐FU treatment induced less severe damage to myenteric neurons with 12% loss at day 14 compared to 25% of myenteric neuronal loss at day 14 of oxaliplatin treatment . Although previous studies demonstrated that the loss of enteric neurons does not necessarily lead to changes in CMMCs our results demonstrated that the loss of myenteric neurons correlated with colonic dysmotility in 5‐FU‐treated mice. The loss of myenteric neurons leads to long‐term alterations in gastrointestinal functions as was shown in rats after cisplatin treatment and mice after oxaliplatin treatment .…”
Section: Discussioncontrasting
confidence: 59%
“…Whilst CMCs do not require intraluminal content, movement of intraluminal content may involve an additional mechanism whereby local polarised neural circuits are sequentially activated by content in a neuromechanical cycle ( Dinning P. G. et al, 2014 ; Costa et al, 2015 ). Indeed, the polarity of intraluminal fluid ( Roberts et al, 2007 ; Roberts et al, 2008 ; Costa et al, 2013 ; Sasselli et al, 2013 ; Wafai et al, 2013 ; Welch et al, 2014 ; Barnes and Spencer, 2015 ; Balasuriya et al, 2016 ; McQuade et al, 2016 ; Robinson et al, 2017 ; Vincent et al, 2018 ; Israelyan et al, 2019 ; Leembruggen et al, 2020 ), and pellet propagation, is virtually always anterograde ( Barnes et al, 2014 ; Balasuriya et al, 2016 ; Diss et al, 2016 ; McQuade et al, 2017 ; Hibberd et al, 2018a ; McQuade et al, 2018 ). In contrast to the loss of anterograde preference in non-propulsive CMCs in CAL-DTR colon in the present study ( Figure 6 ), there was no difference in propagating contraction direction between control and CAL-DTR colon during natural pellet expulsion: nearly all contractions in both groups propagated anterogradely.…”
Section: Discussionmentioning
confidence: 99%
“…This is opposite to the effects observed in murine experimental models that cause non-specific (cholinergic and non-cholinergic) myenteric neuronal losses in the colon. These include chemotherapeutics ( Wafai et al, 2013 ; McQuade et al, 2016 ; McQuade et al, 2017 ; McQuade et al, 2018 ; Stojanovska et al, 2018 ; McQuade et al, 2019 ), colitis ( Robinson et al, 2017 ; Hofma et al, 2018 ), and disrupted endothelin-3 signalling ( Ro et al, 2006 ; Roberts et al, 2008 ; Barnes and Spencer, 2015 ), all of which decrease CMC frequency. Pharmacological blockade of nitric oxide signalling is well known to increase the CMC frequency ( Fida et al, 1997 ; Powell and Bywater, 2001 ), while the effect of genetic knockout is equivocal ( Dickson et al, 2010 ; Spencer, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Video recordings from each animal were used to generate spatiotemporal maps of colonic contractions. Frequency, length and velocity of colonic migrating motor complexes (CMMCs) were analyzed from the spatiotemporal maps using the GIMM processor plugin (Image J) 51,52 . Measurements were made from three 10-minute recordings per mouse and 4–6 mice were analyzed from each group.…”
Section: Methodsmentioning
confidence: 99%